PENGARUH PENGGUNAAN GADGET TERHADAP KONSENTRASI BELAJAR MATEMATIKA PADA SISWA SMA AL-ISHLAH - Muhammad Hasib; Suriyana Suriyana; Riyanti Nurdiana (Cendikia: Jurnal Pendidikan dan Pengajaran, 2023)
This research aims to determine the effect of using gadgets on the concentration of Al-Ishlah High School students in learning mathematics. The research design is descriptive, while the research method is quantitative. Gadget use is the independent variable (X), while study concentration is the dependent variable (Y). Participants in this research population are all 60 Al-Ishlah High School students, 27 male students and 33 female students who form the student body. All 60 participants in this research were Al-Ishlah High School students. The method of collecting samples is non-probability (sampling that does not provide an equal chance or opportunity for each element or member of the population to be selected as a sample). In this research, researchers used the method of determining saturated samples or total sampling. Regarding the data collected using questionnaires, the validity and reliability of the test instruments used in this research were then assessed. normality test, and linearity test, are used to evaluate data analysis requirements. Meanwhile, simple regression analysis and the coefficient of determination test are used to test the hypothesis. Based on the research findings and discussion, the following conclusion can be drawn: there is an influence of gadget use on students' ability to concentrate on learning mathematics at Al-Ishlah High School. This is shown by the results of a significance level of 0.04% < 0.05% with a value of Tcount = 8.977 which is greater than Ttable = 1.671, while the results of the coefficient of determination test show an influence (R) of -0.366 while the value (R square) is 0.134, which means shows that there is an independent negative influence (gadget use) on the dependent variable (learning concentration) of 13.4% while 86.6% is influenced by other variable.